If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 5x = -8 + 6 + 9x Combine like terms: -3x + 5x = 2x 2x = -8 + 6 + 9x Combine like terms: -8 + 6 = -2 2x = -2 + 9x Solving 2x = -2 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. 2x + -9x = -2 + 9x + -9x Combine like terms: 2x + -9x = -7x -7x = -2 + 9x + -9x Combine like terms: 9x + -9x = 0 -7x = -2 + 0 -7x = -2 Divide each side by '-7'. x = 0.2857142857 Simplifying x = 0.2857142857
| -16t^2+96t+176=0 | | 3x^5-13x^4-29x^3+83x^2+66x-30=0 | | x^4-2x^2(x-2)+x^2-4x+4= | | 24=18-2g | | t^2-6t-11=0 | | 44-4h=12 | | 2+4x=-16 | | x=(x+1)(x+3) | | 91-x=171 | | x=x+1x+3 | | x^2+8ix-16=0 | | 166=4(x+20) | | 75n+30=375 | | 2x+4x=2x+36 | | (3x-5)+x+201=125 | | 12(x-7)=26-2 | | (3x-5)x+201=125 | | z^2+zw+w^2=0 | | z^2-2zw+w^2=0 | | -4(x-6)=-10 | | x^2-ix+6=0 | | -2(x+3)=-2 | | 2(p+10)=4 | | 81y^3-16y=0 | | 6(m-6)=5 | | 9y^3-4y^2=0 | | 2(7h-8)=-18 | | 3(x+6)=-10 | | -26=2k+4k | | 105-5x=9x-23 | | 3(1-7d)=33 | | 3(n-5)=14 |